Hypersensitivity with Inhalational Budesonide: An Under Recognised Entity - Pramod Kumar Sharma; Neeraj Gupta; Najmul Hasan; Bhaskar Krishnamurthy; Surjit Singh (Journal of Clinical and Diagnostic Research, 2016)
Hypersensitivity reactions are commonly encountered with drugs such as beta lactams, sulphonamides, allopurinol etc., Corticosteroids are frequently employed in the treatment of drug induced allergic reactions. Therefore, it is highly unlikely that a corticosteroid itself may cause such a reaction as an adverse effect. We had encountered a rare case of hypersensitivity reaction with inhalational budesonide in an eight-year-old boy. The patient developed maculopapular rashes over the back, buttocks and legs accompanied with pruritus within four hours of administration of the first dose. The reaction subsided within two days on withdrawal of the drug and treatment with oral fexofenadine. Re-introduction of budesonide by the same route after a month resulted in appearance of similar reaction. Both the parents of the patient were known cases of allergic rhinitis suggesting allergic pre-disposition in the family. Causality analysis using WHO-UMC scale suggested certain association of this allergic reaction with inhaled budesonide.